2010
DOI: 10.1172/jci42551
|View full text |Cite|
|
Sign up to set email alerts
|

Peripheral CB1 cannabinoid receptor blockade improves cardiometabolic risk in mouse models of obesity

Abstract: Obesity and its metabolic consequences are a major public health concern worldwide. Obesity is associated with overactivity of the endocannabinoid system, which is involved in the regulation of appetite, lipogenesis, and insulin resistance. Cannabinoid-1 receptor (CB 1 R) antagonists reduce body weight and improve cardiometabolic abnormalities in experimental and human obesity, but their therapeutic potential is limited by neuropsychiatric side effects. Here we have demonstrated that a CB 1 R neutral antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
267
2
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(285 citation statements)
references
References 64 publications
12
267
2
4
Order By: Relevance
“…We confirmed that rats strongly prefer emulsions containing 18:2 FA (5% + 20% vol/vol mineral oil) to those containing only mineral oil (25% vol/vol) in the 30 min sham two-bottle choice test [46]. We then pretreated separate groups of sham feeding rats with the peripherally restricted CB 1 R antagonists, AM6545 [8587], or URB447 [38, 88], and presented 18:2 FA and mineral oil emulsions in the sham two-bottle choice test. Blocking peripheral CB 1 Rs inhibited the robust preferences displayed for 18:2 FA versus mineral oil alone.…”
Section: Orosensory Qualities Of Fats and The Endocannabinoidsmentioning
confidence: 71%
“…We confirmed that rats strongly prefer emulsions containing 18:2 FA (5% + 20% vol/vol mineral oil) to those containing only mineral oil (25% vol/vol) in the 30 min sham two-bottle choice test [46]. We then pretreated separate groups of sham feeding rats with the peripherally restricted CB 1 R antagonists, AM6545 [8587], or URB447 [38, 88], and presented 18:2 FA and mineral oil emulsions in the sham two-bottle choice test. Blocking peripheral CB 1 Rs inhibited the robust preferences displayed for 18:2 FA versus mineral oil alone.…”
Section: Orosensory Qualities Of Fats and The Endocannabinoidsmentioning
confidence: 71%
“…The association of increased feeding with cannabis use resulted in the development of CB 1 receptor antagonists/inverse agonists for weight loss and the approval (later retracted because of the potential for psychiatric side effects) of the ligand rimonabant (65). Despite this, the contribution of CB 1 receptors to energy balance and fat storage in the periphery has suggested that peripherally restricted CB 1 receptor antagonists/inverse agonists might well have clinical potency without the central nervous system liabilities (65)(66)(67). Peripherally restricted CB 1 agonists have also been promoted as potential therapeutic agents in both inflammatory and neuropathic pain (55).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, because of the adverse side effects found in the clinical use of Rimonabant (a CB1 antagonist/inverse agonist capable of crossing the blood-brain barrier) for the management of obesity complications, peripheral-restricted CB1 antagonists are becoming a hottopic in the search for new drugs against obesity-related diseases (Bermudez-Silva et al 2010). Indeed, some of these new kinds of drugs have recently shown promising results in animal studies (Tam et al 2010). Interestingly, Rimonabant and AM251 (another CB1 antagonist/inverse agonist capable of crossing the blood-brain barrier) have been reported to activate GPR55, suggesting that some of the effects elicited by these drugs could be mediated by this receptor (Kapur et al 2009, Henstridge et al 2010.…”
Section: Introductionmentioning
confidence: 99%